A comparative study on the performance of MIMO‐STBC subject to Weibull fading channels - El Bouanani, Faissal; Bessate, Abdelmajid (International journal of communication systems, 2018)
Summary In this paper, we investigate the analytical performance of the multiple‐input multiple‐output system (MIMO) with orthogonal space‐time block codes (STBCs) subject to Weibull fading channels (WFC). Space‐time block code technique provides an efficient pattern for wireless transmission over various fading channels using multiple transmit antennas. Two approximating methods of the sum of independent Weibull random variables are studied. For each approach, we derive accurate approximate expressions for several performance metrics of MIMO‐STBC system operating under independent and nonidentical WFC. The proposed approximations are expressed in terms of 2 generalized hypergeometric functions, namely, Fox's H and Meijer's G functions. All the derived approximate expressions prove high accuracy, while compared with the simulation results established via Monte Carlo method and Kolmogorov‐Smirnov test as well. Although the 2 approaches have approximately the same accuracy, the second method approximate expressions are much less complex than those of the first method. In this paper, 2 tight approximate Weibull sums PDF have been used to figure out the performance of MIMO‐STBC system subject to uncorrelated Weibull fading channel. The results show that the 2 methods are accurate, whereas the evaluation time of analytical expressions derived using the first approach is less than the second one.